Numerical simulation of ship collision with gravity base foundations of offshore wind turbines - Hamann, Thorben; Pichler, Torben; Grabe, Jürgen (Volume 6: Polar and Arctic Sciences and Technology; Offshore Geotechnics; Petroleum Technology Symposium, 2013)
For the installation of offshore foundations several countries (e.g. Germany) require a proof of averting environmental disasters in case of ship collision. The aim is to prevent possible discharge of supplies or even loss of the vessel. Especially for gravity base foundations this load case is problematic due to their larger stiffness and mass compared to monopiles, tripods or jacket foundations. The finite element method provides a powerful tool to predict the collision behaviour in a realistic way taking into account the complex interaction between vessel, foundation and soil. The collision between a fully loaded single hull tanker and a gravity base foundation is subject of numerical analysis. The calculated contact forces between vessel and foundation are compared to a simplified calculation approach. For evaluation of the foundation deformations and areas of failure of the vessel are investigated. The influence of the water depth, the diameter of the foundation and an embedment in the seabed are determined in a parametric study. It can be shown that the finite element method is a suitable approach for investigation of the collision behaviour of offshore structures. The design of gravity base foundations can be optimized with respect to ship collision in a fast and cost-effective manner using this method.